2015
DOI: 10.1063/1.4921423
|View full text |Cite
|
Sign up to set email alerts
|

Achieving enhanced and tunable adhesion via composite posts

Abstract: Surfaces with enhanced and tunable adhesion have a variety of applications, including microtransfer printing of semiconductor elements, material handling in manufacturing, and gripping surfaces on climbing robots. Traditionally, schemes to achieve tunable adhesion have relied on fabricating arrays of posts or fibers with complex geometries, such as angled posts terminated by wider caps. Here, we describe an alternative to post structures with complex geometries through the use of composite posts that consist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 29 publications
4
72
2
Order By: Relevance
“…(45,46) As the thickness of the PDMS layer on top of the stiff core is decreased, the maximum stress shifts to the center and the detachment force increases. (45) Considering the strong interfacial bonding between the PS nanopillars and PDMS matrix (Comp+) in the structures investigated here, the PS/PDMS composite effectively acts as a stiff core, similar to the previous work discussed above. However, the discrete nature of the PS nanopillars may affect the stress distribution, thus we investigated our structure using finite element analysis ( Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…(45,46) As the thickness of the PDMS layer on top of the stiff core is decreased, the maximum stress shifts to the center and the detachment force increases. (45) Considering the strong interfacial bonding between the PS nanopillars and PDMS matrix (Comp+) in the structures investigated here, the PS/PDMS composite effectively acts as a stiff core, similar to the previous work discussed above. However, the discrete nature of the PS nanopillars may affect the stress distribution, thus we investigated our structure using finite element analysis ( Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…30 In addition, numerical simulations revealed that the stress distribution along the pillar–substrate interface dramatically varied with the soft layer thickness, Young’s modulus ratio, and materials interface curvature as shown in Supporting Information Figure S1. Particularly, the stresses at the center of the fibril increased with decreasing soft layer thickness, i.e., increasing confinement.…”
Section: Discussionmentioning
confidence: 99%
“…29 Recently, first experimental and numerical studies have been performed for fibrils with axial variations of the Young’s modulus adhering to smooth surfaces. 30 It was found that very thin soft tip layers promise the best adhesion enhancements for smooth substrates. Interestingly, Bae et al demonstrated that a soft tip coating added to a micropatterned fibrillar array improved adhesion to skin, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the unique properties of adhesive surfaces found in nature, micropatterned adhesives are currently under intense research for handling fragile and miniaturized objects, even in demanding environments such as vacuum . Among the various designs, microstructures with mushroom‐shaped tips have an exceptionally high adhesion . It was demonstrated that their pull‐off force, i.e., the force necessary for detaching the adhesive from a substrate, was up to an order of magnitude higher than with nonoptimized flat punch pillars .…”
Section: Introductionmentioning
confidence: 99%